(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2015)
This article approaches the international trafficking in persons and the challenges it represents. It also proposes ways to deal with the trafficking through the regional integration instruments as well as the economic logic of crime fundaments. As a transnational crime, trafficking crosses borders and involves several countries, representing a hard obstacle to be handled by governments. Focusing efforts on repression hasn’t led to a solution because the roots of trafficking are in poverty and social development. That’s why it should be faced by preventive efforts. Within this view, a human rights-based approach is more likely to succeed. From those perspectives, this paper suggests that States should establish cooperation through regional integration bodies, especially in UNASUR, and that society should boycott products made with slave labor. Therefore, the purpose is to provoke a critical thinking about trafficking in persons and try to build new alternatives for achieving effective results.